Effects of different goal orientations and virtual opponents performance level on pacing strategy and performance in cycling time trials. Issue 4 (3rd April 2022) - Crivoi do Carmo, Everton; Renfree, Andrew; Nishimura Vieira, Caio Yudi; Ferreira, Diego dos Santos; Truffi, Gabriel Abrahão; Barroso, Renato
ABSTRACT: We investigated the effects of different performance goals (best time vs. beat the opponent) on pacing behaviour during a 10-km cycling race and explored the influence of different performance level of opponents on ratings of perceived exertion (RPE), affective feelings and self-efficacy. Thirteen cyclists performed two time-trials (TT) and two races against a faster (FAST +6%) or a slower (SLOW –3%) virtual opponent. Power output (PO), RPE, affective feelings and self-efficacy were recorded at each kilometre point. Race average and race phases [starting (P1 = first kilometre); first half (P2 = 2nd–5th kilometre); second half (P3 = 6th–9th kilometre) and final sprint (FS = last kilometre)] were analysed. There was no difference in performance, assessed by race time between conditions ( p  = .84). PO during TT was lower in P3 compared to FS ( p  = .03; ES 0.6; 90%CI 0.4–0.7). In SLOW and FAST, PO was higher in P1 compared to other phases ( p  < .05). PO in FS was higher in TT compared to FAST ( p  = .01; ES −0.97; 90%IC −1.4 to −0.5). RPE increased and affective feelings decreased during all conditions. Self-efficacy was stable through TT and SLOW, but decreased during FAST with higher values in P1 compared to P2 ( p  = .01; ES −1.1; 90%IC −1.6 to −0.6), P3 ( p  < .001; ES −2.2; 90%IC −2.8 to −1.6) and FS ( p  < .001; ES −2.6; 90%IC −3.3 to −1.8). Pacing behaviour, specifically starting and final sprint, was affected by virtual opponents independent of performance level, demonstrating the importance of goal orientation. Highlights Adjustments in exercise intensity result from a complex decision-making process involving physiological, psychological, environmental and tactical information. Goal pursuit is an important determinant of pacing behaviour since athletes must balance their efforts with expectations of success. A competitive environment may be included to motivate participants to maintain their effort and at the same time to improve their self-confidence. The presence of a final sprint seems to be related to the goal orientation and perceived outcomes of success or failure.